Technical and clinical outcomes of 13 years of endovascular repair of infrarenal, atherosclerotic, penetratingaortic ulcers - Hatzl, Johannes; Fiering, Jonathan; Barb, Alexandru; Körfer, Daniel; Bornhak, Louisa; Peters, Andreas; Uhl, Christian; Böckler, Dittmar (Annals of vascular surgery, 2025)
Background - To report the technical and clinical outcomes of endovascular repair of all infrarenal, penetrating aortic ulcers (PAUs) that were treated at a single institution over a 13-year period. - Methods - This is a single-center, retrospective observational study. All patients consecutively treated for atherosclerotic, infrarenal PAU were included between 2010 and 2023. Outcomes were technical success, overall survival, PAU-related death, freedom from secondary rupture, freedom from secondary interventions, freedom from aortic expansion >5 mm, freedom from type 1 and type 3 endoleak (EL), and freedom from stent graft migration, each at 30 days, 1 year, 2 years, and 5 years of follow-up. The study was registered at the German Clinical Trials Register (DRKS00028794). - Results - Forty-seven patients were included (8 female patients, 17.0%) with a median age of 75.7 years (interquartile range (IQR): 70.2-81.0). The median maximum aortic diameter was 39.7 mm (IQR: 33.6-45.2). Overall, primary and secondary technical success was achieved in 42 of 47 (89.4%) and 46 of 47 patients (97.9%). Standard aortobiiliac endovascular aneurysm repair (EVAR) was the most frequent procedure in 25 patients (53.2%). An aortomonoiliac stent graft system was used in 5 patients (10.6%). The remaining 17 patients (36.2%) were treated using an aorto-aortic tube stent graft configuration. The median clinical follow-up was 5.1 years (IQR: 1.9-8.1) with a median imaging follow-up of 1.5 years (IQR: 0.4-5.0). Overall survival at 30 days, 1, 2, and 5 years of follow up was estimated at 100% (confidence interval (CI), 100%-100%), 95.4% (CI, 89.4%-100%), 87.9% (CI, 78.4%-98.4%), and 82.0% (70.7%-95.2%), respectively. There was 1 PAU-related death (2.1%). Freedom from secondary intervention at 30 days, 1, 2, and 5 years of follow-up was 93.6% (CI, 86.9-100%), 89.2% (CI, 80.6-98.6%), 81.5% (CI, 70.7-94.0%), and 75.2% (CI, 62.8-90.2%), respectively. No patient who underwent either preoperative (n = 1) or intraoperative embolization (N = 7) of lumbar arteries (LAs) and/or the inferior mesenteric artery (IMA) demonstrated type 2 EL during follow-up. - Conclusion - A variety of alternatives to standard aortobiiliac EVAR are required for endovascular PAU repair. To identify the optimal management strategy in these cases further studies are needed. Type 2 EL in abdominal PAU disease appears to be preventable by LA and/or IMA embolization.